OPTIMIZING COMMUNITY PARTICIPATION TO STRENGTHEN COLLABORATIVE GOVERNANCE IN ADDRESSING URBAN ISSUES IN BEKASI - Evi Mafriningsianti; Sandi Setiadi (RADJA PUBLIKA, 2026)
The paradigm shift from government to governance requires the active involvement of the community as partners in addressing complex urban issues such as flooding and waste management. This study aims to analyze the influence of community participation on collaborative governance and the effectiveness of urban problem handling in the city of Bekasi. The novelty of this study lies in placing the community as the main unit of analysis to fill the gap in previous studies that tended to focus on the perspective of government institutions. The research method used is quantitative explanatory with Structural Equation Modeling (SEM-PLS) analysis techniques. Data were collected from 130 respondents in Bekasi City through purposive sampling. The results of hypothesis testing show that community participation has a very strong positive influence on strengthening collaborative governance (t=34.897). Furthermore, collaborative governance has a significant effect on the effectiveness of urban problem handling (t=3.440). Although citizen participation has a direct impact on effectiveness (t=2.299), the role of collaborative governance as a mediating variable is proven to be vital in optimizing citizen contributions into real and sustainable solutions (t=3.461). These findings confirm that substantive participation through equal dialogue spaces is the key to successful modern city governance.